2016
DOI: 10.1377/hlthaff.2016.0578
|View full text |Cite
|
Sign up to set email alerts
|

Many Mobile Health Apps Target High-Need, High-Cost Populations, But Gaps Remain

Abstract: With rising smartphone ownership, mobile health applications (mHealth apps) have the potential to support high-need, high-cost populations in managing their health. While the number of available mHealth apps has grown substantially, no clear strategy has emerged on how providers should evaluate and recommend such apps to patients. Key stakeholders, including medical professional societies, insurers, and policy makers, have largely avoided formally recommending apps, which forces patients to obtain recommendati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
138
1
3

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(147 citation statements)
references
References 11 publications
5
138
1
3
Order By: Relevance
“…While prior studies have used 10-point scales to assess quality,15 we felt that a simpler scheme of (a) ‘serious concerns regarding safety’, (b) ‘appears acceptable’ and (c) ‘may be useful or offer more features than other similar apps’ offers higher validity, though still subjective in nature. Any apps that raised concern about the safety of the user were rated as ‘serious concerns regarding safety’ (eg, apps that installed malware on the user’s phone, apps that promise brain changes after listening to music and so on).…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…While prior studies have used 10-point scales to assess quality,15 we felt that a simpler scheme of (a) ‘serious concerns regarding safety’, (b) ‘appears acceptable’ and (c) ‘may be useful or offer more features than other similar apps’ offers higher validity, though still subjective in nature. Any apps that raised concern about the safety of the user were rated as ‘serious concerns regarding safety’ (eg, apps that installed malware on the user’s phone, apps that promise brain changes after listening to music and so on).…”
Section: Methodsmentioning
confidence: 95%
“…Although there is some evidence that there is a correlation between star rating of an app and its number of downloads,14 generally little is known about why some health apps become popular and others not. Furthermore, researchers have demonstrated that the number of stars or number of downloads on app marketplaces does not correlate with clinical utility or validity for all apps including mental health apps 15. Ideally better features and functionality would drive popularity, but research on popular blood pressure apps suggests that those offering inaccurate and ‘falsely reassuring’ low numbers were top rated, presumably because people liked being told that they were healthy 16.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, there are on-line star ratings by users but a study of 137 patient-facing apps found that star-based ratings had low correlation with the apps’ clinical utility or usability. 50 Clinical ratings of individual features of mental health apps also show low interrater reliability 51 and the frequently updating nature of apps means any static score for them will be rapidly out of date. There may be utility in using smartphone app evaluation frameworks in future research whereby both doctors and patients have tools to weight the risks, evidence, usability, and data sharing potential of an app.…”
Section: Discussionmentioning
confidence: 99%
“…Presently, the mHealth field is at a crossroads: the cell phone medium is at risk of losing its utility for public health delivery due to the dearth of research evaluating the effectiveness of the over 100,000 available, predominantly consumer-facing mobile apps [27,28]. Sense Health has integrated health behavior theory into the development of its mobile communication platform from the outset, thus presenting an opportunity to assess the implications of using a theory-based approach.…”
Section: Introductionmentioning
confidence: 99%